1978
DOI: 10.1177/000331977802901103
|View full text |Cite
|
Sign up to set email alerts
|

Premature Hair Graying: A Probable Coronary Risk Factor

Abstract: Hypertension, diabetes mellitus, hypercholesterolemia, and smoking are known coronary risk factors. It has been our impression that premature graying of the hair also predisposes individuals to myocardial infarctions. To test this hypothesis, we evaluated all of the patients under the age of 50 who were admitted to the coronary care unit between 1974 and 1976 with a proven diagnosis of a myocardial infarction. There were 50 patients. Thirty-eight did not have premature graying. Twelve of the male patients (24%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 0 publications
3
31
1
Order By: Relevance
“…In the present study there was a huge societal misconception that gray hair sufferers were older of their age. Similar findings were reported previously [17]. This fact has been reported to have a far-reaching effect to the sufferers in the society from social stigma to difficulties in getting spouses and marriage [2].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study there was a huge societal misconception that gray hair sufferers were older of their age. Similar findings were reported previously [17]. This fact has been reported to have a far-reaching effect to the sufferers in the society from social stigma to difficulties in getting spouses and marriage [2].…”
Section: Resultssupporting
confidence: 90%
“…The pattern of scalp regional graying development did not essentially differ between sexes but more males (75.5%) had hair graying initially involving the parietal areas than in the females whose regional graying patterns were mostly equally distributed all over the scalp regions. behaviors such as smoking and sedentary life style were reported by a huge proportion of participants [8,15,16] whereas some other studies established a weak association or no association at all [17]. The consequential psychological effects to the sufferers were enormous among the participants of the present study.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Our findings also supported these observations and detailed them. Afterwards, subsequent studies with various sample sizes were performed in different patient populations including CAD, myocardial infarction in black or white men or women (5)(6)(7)(8)(9)(10)(11). Several of these reports also showed association between premature hair whitening and myocardial infarction, although many are relatively outdated and have some methodological limitations, especially in determining the extent of CAD and intensity of hair whitening.…”
Section: Discussionmentioning
confidence: 99%
“…All of these pathological microenvironments can be produced by CVRFs (11), which can induce premature vascular aging and atherosclerosis. In prior studies, premature hair graying has also been reported to be associated with CVRFs (12)(13)(14)(15), CAD and myocardial infarction (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 97%